A Critical Review of the Model Minority Myth in Selected Literature on Asian Americans and Pacific Islanders in Higher Education. (June 2016) - Poon, OiYan; Squire, Dian; Kodama, Corinne; Byrd, Ajani; Chan, Jason; Manzano, Lester; Furr, Sara; Bishundat, Devita
This article presents a critical review of 112 works of research on Asian Americans and Pacific Islanders (AAPIs) in higher education. It focuses on ways previous scholarship framed AAPIs in higher education, and specifically on how those works engaged in a sustained project of countering the model minority myth (MMM). Many publications on AAPIs in higher education mentioned the MMM and neglected to account for the original purpose of the MMM—to maintain anti-Black racism and White supremacy. We identified four key and interconnected limitations implicit in the counter-MMM framework that result from a lack of a critical recognition of the model minority as an instrument to maintain White dominance. Our analysis suggests that the well-established counter-MMM scholarly project is fundamentally flawed in its ability to humanistically reframe and advance research on AAPIs. Therefore, we call for a reframing of research on AAPIs in higher education.